Comparison of stress distribution of TMJ with different mandibular deformities under incisal clenching. Issue 2 (3rd February 2022) - Li, Annan; Shao, Bingmei; Liu, Zhan
Abstract: Temporomandibular joint (TMJ) is an important and complex joint in the human body. It is necessary to explore the biomechanical influence on the TMJs caused by different mandibular deformities. The maxillofacial models from 34 subjects were built to analyze the maximum and minimum principal stresses of the TMJs in the control group and three test groups. The results showed that only the deviation group had statistical differences between both sides. And these mandibular deformities decreased the tensile stresses of the temporal bones and increased the compressive stresses of the condyles and the discs. The patients with mandibular deviation had most risk with TMD.